RpoS Regulates Essential Virulence Factors Remaining to Be Identified in Borrelia burgdorferi - Xu, Qilong (Public Library of Science, 2012)

(untitled)
BACKGROUND: Since the RpoN-RpoS regulatory network was revealed in the Lyme disease spirochete Borrelia burgdorferi a decade ago, both upstream and downstream of the pathway have been intensively investigated. While significant progress has been made into understanding of how the network is regulated, most notably, discovering a relationship of the network with Rrp2 and BosR, only three crucial virulence factors, including outer surface protein C (OspC) and decorin-binding proteins (Dbps) A and B, are associated with the pathway. Moreover, for more than 10 years no single RpoS-controlled gene has been found to be critical for infection, raising a question about whether additional RpoS-dependent virulence factors remain to be identified. METHODOLOGY/PRINCIPAL FINDINGS: The rpoS gene was deleted in B. burgdorferi; resulting mutants were modified to constitutively express all the known virulence factors, OspC, DbpA and DbpB. This genetic modification was unable to restore the rpoS mutant with infectivity. CONCLUSIONS/SIGNIFICANCE: The inability to restore the rpoS mutant with infectivity by simultaneously over-expressing all the three virulence factors allows us to conclude RpoS also regulates essential genes that remain to be identified in B. burgdorferi.